The Effect of Educative Supportive Program Using Line Application on Diabetes Prevention in Prediabetes Among Hospital Personal - Nasin, Minraya; Kimsungnoen, Nipa (Journal of The Royal Thai Army Nurses, 2026)
This research is quasi-experimental one-group pretest-posttest design to examine The Effect of Educative Supportive Program Using Line Application on Diabetes Prevention in Prediabetes Group. The sample consisted of 22 persons with prediabetes who participated in the program, which was based on Orem’s self-care theory. Data were collected on self-care behaviors and fingertip fasting blood glucose levels, were collected before and after the program and analyzed by descriptive statistics, paired t-test Wilcoxon Signed Rank test and Mcnemar’s test. The research results showed that the average scores of the participants significantly improved after receiving the program compared to before (p < .001). Additionally, blood glucose levels were significantly reduced after participating in the program (p < .001).